Novel fabrication technologies of 1D TiO2 nanotubes, vertical tin and iron–based nanowires for Li–ion microbatteries. (7th February 2012) - Ortiz, Gregorio F.; Hanzu, Ilie; Lavela, Pedro; Knauth, Philippe; Djenizian, Thierry; José,
We present the combination of anodisation, sputtering and electrodeposition processes as a novel technology to fabricate nanoarchitectured materials. Titania nanotubes are successfully fabricated using Ti foils and Ti film on Si wafers; by simply varying the anodisation parameters a 600–900 nm range of tube length and a 50–150 nm range of tube diameter can be obtained. Iron and tin oxides nanowires, microballs, microcubes or with sponge–like morphology are obtained showing that the crystallinity can be tuned by optional heat treatment, but the initial morphology is preserved. We investigate all these materials as alternative electrodes for lithium–ion batteries and microbatteries. It should be highlighted the fabrication of vertical nanowires using a template–free approach exhibits some advantages because the electroactive species are fabricated directly onto the current collector, ensuring good electrical contact between titania nanotube layers and the current collector, and tackle the use of additives such as binder and conductive agents. Thus, Sn on an amorphous titania matrix and SnO nanowires on a crystalline titania matrix with a particular geometry (2 µm of tin/tin oxide length) have a remarkable reversible capacity of about 140 µA h cm −2 (675 mA h g −1 and 70 µA h cm −2 µm −1 ) which is kept about 85% over 50 cycles. The matrix presented here can allow the volume expansion of lithium–tin alloys and thus enhances the electrochemical performances as compared with usual tin–based electrodes. In the text is also described the electrochemistry of a series of samples such as a 3 µm thick nanocomposite made of vertical iron oxide nanowires with quite regular form and diameters ranging between 20 nm and 150 nm grown on a matrix of self–organised TiO2 nanotubes. The obtained capacities compare very favourably with the best literature data for Li–ion microbatteries.